MENUMBUHKAN BAKAT ANAK SEKOLAH DASAR DI LINGKUNGAN KELUARGA (ANALISIS BUKU ORANGTUANYA MANUSIA KARYA MUNIF CHATIB) - Dea Rakhimafa Wulandari (Sekolah Tinggi Pendidikan Islam (STPI) Bina Insan Mulia Yogyakarta, 2019)
Talent is an activity that is liked by children who come from internal. Talent is not formed by a combination of supporting aspects. One aspect is the family environment. The purpose of this study was to determine the concept of growing children's talents in the family environment according to Munif Chatib and to determine the role of parents in growing children's talents according to Munif Chatib,. The method used in this study was a qualitative approach with analytical library types. descriptive. Data collection techniques using the technique of documentation and content analysis. This method is used to find out Munif Chatib's thoughts about the concept of growing elementary school age talent in a family environment. Based on data analysis, it was found that (1) the concept of growing elementary school talent in a family environment according to Munif Chatib is not to make the home as a child talent killing machine; (2) the role of parents in developing talent according to Munif Chatib as an educator, motivator, facilitator and as a model.